Electroencephalographic, cognitive, and neurochemical effects of LY3130481 (CERC-611), a selective antagonist of TARP-γ8-associated AMPA receptors. (November 2017) - Witkin, Jeffrey M.; Li, Jennifer; Gilmour, Gary; Mitchell, Stephen N.; Carter, Guy; Gleason, Scott D.; Seidel, Wesley F.; Eastwood, Brian J.; McCarthy, Andrew; Porter, Warren J.; Reel, Jon; Gardinier, Kevin M.; et al.
Abstract: 6-[(1S)-1-[1-[5-(2-hydroxyethoxy)-2-pyridyl]pyrazol-3-yl]ethyl]-3H-1, 3-benzothiazol-2-one (LY3130481 or CERC-611) is a selective antagonist of AMPA receptors containing transmembrane AMPA receptor regulatory protein (TARP) γ−8. This molecule has been characterized as a potent and efficacious anticonvulsant in an array of acute and chronic epilepsy models in rodents. The present set of experiments was designed to assess the effects of LY3130481 on the electroencephelogram (EEG), cognitive function, and neurochemical outflow. LY3130481 disrupted food-maintained responding in rats and spontaneous alternation in a Y-maze in mice. In rat fear conditioning, LY3130481 caused a deficit in trace (hippocampal-dependent), but not in delay fear conditioning. Although these effects on cognitive performances were observed, the known cognitive-impairing anticonvulsant, topiramate, did not always produce deficits under these assay conditions. LY3130481 produced modest increases in wake times in rats. In addition, LY3130481 was able to attenuate some impairing effects of standard antiepileptic drugs. The motor-impairing effects of the lacosamide were attenuated by LY3130481 as was the decrease in non-rapid-eye movement sleep induced by carbamazepine. Evaluation of the effect of LY3130481 on neurotransmitter and metabolite efflux in the rat medial prefrontal cortex, using in vivo microdialysis, revealed significant increases in the pro-cognitive and wake-promoting neurotransmitters, histamine and acetylcholine, as well as in serotonin, telemethylhistamine, 5-HIAA, HVA and MHPG. LY3130481 thus presents a novel behavioral profile that will have to be evaluated in patients to fully appreciate its implications for therapeutics. LY3130481 is currently under clinical development as CERC-611 as an antiepileptic. Highlights: LY3130481 (CERC-611) is a selective antagonist of AMPA receptors TARP γ−8 protein. LY3130481 is currently under clinical development as CERC-611 as an antiepileptic. LY3130481 produced mixed results in rodent cognition assessments. LY3130481 produced modest increases in wake times in rats and increased wake and cognition-associated neurotransmitters. LY3130481 attenuated some impairing effects of standard antiepileptic drugs.